Aberrant B-cell homeostasis in chronic GVHD - Sarantopoulos, Stefanie (Blood, 2015)
Recent studies have compelled further interest in the potential pathological role of B cells in chronic graft-versus-host disease (cGVHD). In patients with cGVHD, B cells are activated and primed for survival via B-cell activating factor and B-cell receptor–associated pathways. Understanding the signaling pathways that drive immune pathology in cGVHD will facilitate the development of new strategies to selectively target aberrantly activated B cells and restore normal B-cell homeostasis after allogeneic stem cell transplantation.